If it's not what You are looking for type in the equation solver your own equation and let us solve it.
21=5(u+3)-7u
We move all terms to the left:
21-(5(u+3)-7u)=0
We calculate terms in parentheses: -(5(u+3)-7u), so:We get rid of parentheses
5(u+3)-7u
We add all the numbers together, and all the variables
-7u+5(u+3)
We multiply parentheses
-7u+5u+15
We add all the numbers together, and all the variables
-2u+15
Back to the equation:
-(-2u+15)
2u-15+21=0
We add all the numbers together, and all the variables
2u+6=0
We move all terms containing u to the left, all other terms to the right
2u=-6
u=-6/2
u=-3
| 0.3+0.2(x+3)=2.5 | | 1/3(4x-9=8x+12 | | 6x+9-3=3x+30 | | 2/3(4x-9=8x+12 | | 0.3+0.2x+3=2.5 | | t25=325 | | 4(7x-1)-5(3x-19)=3(4x+4)-1 | | 3/2x+1=360 | | m/9=^24/^36 | | p=63/7+63 | | (X)x.22=34000000 | | x^2+4x-349=0 | | t=88/8+88 | | P(x)=3x^2-5x | | 2x/7=-1/2 | | 19=u/4+13 | | 3t+6+4t-6t=1+4 | | 42=6(k+3) | | -11=3+k | | -7+8b=-11+8b+8-4 | | -12p+3p=11(p+14) | | x*x=180 | | y(2y+1)+10=0 | | 5x^2+6x=-3x^2+2x | | 42=6k+3 | | (x-1)^3=8 | | -12=a-2 | | j/6+41=45 | | 96=8(n+1) | | 2h+4-55=-3h+4 | | 5x+14=109 | | Y=117.8+-1.4x |